Post-Bariatric surgery: six surgeries in two steps - José Carlos Daher; Amanda Costa Campos; Marcela Caetano Cammarota; Bruno Esteves Peixoto; Gabriel Campelo dos-Santos; Leonardo David Pires Barcelos; Ronan Caputi Silva Dias; Leonardo Martins Costa Daher (Revista Brasileira de Cirurgia Plástica, 2019)
Introduction: Weight reduction achieved after bariatric surgery can result in deformities of various parts of the body. The need for reduction of leftover skin and body remodeling makes patients seek body contouring surgery to improve their quality of life. The aim of the study was to present a protocol for post-bariatric plastic surgery at Daher Hospital. Methods: This was a retrospective longitudinal observational study. As routine protocol, we divided the procedures into two steps, performed in different surgical stages, which we termed the two-level principle. Herein we describe the routine of pre, intra, and postoperative care, as well as details of the surgical techniques. Photographic images were analyzed by an external evaluator. Results: The study included 13 ex-obese patients, with a mean age of 44 years. Of them, 6 patients underwent lower- and upper-level surgeries and another 6 underwent lower-level surgeries. The mean surgical time for the lower level was 4 hours and 54 minutes and that for the upper level was 4 hours and 5 minutes. A total of 92.30% of the patients were satisfied with the results. An external evaluator classified 92.30% of the cases as good or great. Conclusion: Circumferential abdominoplasty has immense benefits and complementary surgeries are vital for a satisfactory result. Reduction of the surgical time requires great synchronization of the surgical team, which allows procedures to be performed simultaneously by multiple surgical teams working in different body parts. Satisfactory results and low complication rates allow the applicability of our routine in post-bariatric patients.